ESSENCE OF BEING: IN A WORLD OF OPTIMUS AND AI. - JEFFERSON, WILLIAM E. (ETC: A Review of General Semantics, 2025)
The article explores the growing influence of artificial intelligence (AI) and advanced robotics on human identity, communication, and society. Topics include the declaration by British novelist Samuel Butler that machines will hold the real supremacy over the world, a complex enigma presented by AIs focused on language and human engagement, and the theory explaining human adaptation of tools and technologies.